2020
DOI: 10.26740/jrba.v2n2.p70-76
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Carbon Sources to Pineapple Waste Media in the Production of Single Cell Protein Biomass Saccharomyces cerevisiae

Abstract: Single-cell protein (SCP) is the term used for crude or pure protein derived from simple single or multi-celled microorganisms. Pineapple peel contains monosaccharides as much as 10.8% so that it can be used as a fermentation medium in single-cell protein production. The purpose of this study was to determine the effect of adding carbon sources of fructose and sucrose on pH, cell dry weight, and protein content in the manufacture of single-cell proteins. This study used a completely randomized design (CRD) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…The overall results indicated that adding protein-rich material is an alternative nutritional and economic method. Nurmalasari et al 64 reported using S. cerevisiae to determine the effect of adding fructose and sucrose on the production of SCP. The results suggest that the addition of sugars to the media had a very significant impact on the pH, protein content and cell dry weight.…”
Section: Literature Description (Table 2) Of Scp Production Using Var...mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall results indicated that adding protein-rich material is an alternative nutritional and economic method. Nurmalasari et al 64 reported using S. cerevisiae to determine the effect of adding fructose and sucrose on the production of SCP. The results suggest that the addition of sugars to the media had a very significant impact on the pH, protein content and cell dry weight.…”
Section: Literature Description (Table 2) Of Scp Production Using Var...mentioning
confidence: 99%
“…The overall results indicated that adding protein‐rich material is an alternative nutritional and economic method. Nurmalasari et al 64 . reported using S. cerevisiae to determine the effect of adding fructose and sucrose on the production of SCP.…”
Section: Literature Description (Table 2) Of Scp Production Using Var...mentioning
confidence: 99%
“…Protein kasar pada kulit ubi meningkat sebesar 59,56% setelah di fermentasi selama 3 hari menggunakan S. cerevisiae [8]. Limbah kulit nanas dengan penambahan fruktosa digunakan sebagai substrat S. cerevisiae dapat menghasilkan SCP sebesar 85,55 mg/L setelah di fermentasi selama 72 jam [9]. Berdasarkan uraian tersebut, diketahui bahwa pakan ternak yang mengandung karbohidrat dapat ditingkatan kandungan proteinnya melalui proses fermentasi menggunakan S. cerevisiae.…”
Section: Pendahuluanunclassified
“…Typically, growth in a liquid culture medium predominantly manifests at the lowermost region of the medium. Typically, sugar molecules have a high degree of fermentation, while nitrates do not undergo assimilation (Nurmalasari & Maharani, 2020).…”
Section: C6h12o6(s) 2c2h5oh (Aq) + 2co2 (G) (Glukosa) Ethanolmentioning
confidence: 99%